About simulation environment for modeling the Internet of Things components and applications using visual flow-based programming tools and cloud services - A. A. Andrushevich; I. S. Vojteshenko; O. Ju. Emelianova (Informatika)
Objectives. The purpose of the analytical and research work was to develop and perform an initial assessment of the capabilities of simulation environment for modeling the Internet of Things (IoT) components and applications. The relevance of the problem is associated with the need to simplify research and testing of such systems as the field is growing. In the implementation of the simulation environment, the following goals were pursued: building a mathematical model; implementation of software, capable of running experiments on that model; providing the user with the ability to analyze results and adjust the model.Methods. Methods of simulation modeling were used.Results. Analysis of the relevance and impact of the research results has led to an appropriate example for demonstrating methods and means of solving the problem of IoT subsystems, components, and applications simulation in the proposed environment. This example has been implemented in the part of the Smart Home application model responsible for the energy efficiency optimization in residential buildings enclosed in a simulation environment based on an integrated software package consisting of the Node-RED visual tool for flow-based programming and the Yandex Cloud / Yandex IoT Core cloud service.Conclusion. A simulation model for managing energy consumption of a "smart home" was developed and implemented using the previously specified software package, including modeling time, environmental conditions, heat loss, operating modes of heating equipment and the behavior of house residents. Based on the implemented model, an initial series of simulation experiments were also carried out, on the one hand, aimed at checking some characteristics of the functionality of the developed simulation environment and the selected example for simulation of residential premises energy management. As a result of the initial experiments, the basic functionality of the integrated software package was proven and demonstrated based on the use of Node-RED and the Yandex Cloud / Yandex IoT Core cloud service for solving problems of simulation modeling of components, subsystems and applications of the Internet of things.